2006
DOI: 10.1063/1.2243973
|View full text |Cite
|
Sign up to set email alerts
|

Recombination processes in midinfrared InGaAsSb diode lasers emitting at 2.37μm

Abstract: The temperature dependence of the threshold current of InGaAsSb/ AlGaAsSb compressively strained lasers is investigated by analyzing the spontaneous emission from working laser devices through a window formed in the substrate metallization and by applying high pressures. It is found that nonradiative recombination accounts for 80% of the threshold current at room temperature and is responsible for the high temperature sensitivity. The authors suggest that Auger recombination involving hot holes is suppressed i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
37
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
3
1

Relationship

4
4

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 17 publications
(18 reference statements)
0
37
0
Order By: Relevance
“…Some suggested that non-radiative Auger recombination is the most detrimental mechanism which limits the performance of the low band-gap longwavelength semiconductor lasers. [19][20][21][22] On the other hand, Shterengas et al 23,24 and Rain o et al 25 reported that thermally induced hole escape is the main non-radiative process which deteriorates the optical properties and performances of the GaSb-based devices at elevated temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Some suggested that non-radiative Auger recombination is the most detrimental mechanism which limits the performance of the low band-gap longwavelength semiconductor lasers. [19][20][21][22] On the other hand, Shterengas et al 23,24 and Rain o et al 25 reported that thermally induced hole escape is the main non-radiative process which deteriorates the optical properties and performances of the GaSb-based devices at elevated temperature.…”
Section: Introductionmentioning
confidence: 99%
“…A similar phenomenon has previously been observed in GaInAsSb lasers operating at 2.37 lm using high pressure techniques. 23 Since the spin-orbit split-off energy is largely controlled by the group V composition, it is relatively insensitive to pressure. Hydrostatic pressure also increases both m so and m e .…”
mentioning
confidence: 99%
“…Figure 1 shows the pressure dependence of the threshold current, I th , of the VCSEL at three different temperatures (-10ºC, 20ºC and 30ºC) and of a reference EEL with the same active region (I th in this case normalised to its value at atmospheric pressure). The decrease in I th with increasing pressure in the EEL indicates that Auger recombination is dominant at room temperature in this materials system and explains the temperature sensitivity of these EELs [3]. In the VCSEL the pressure dependence of I th is much more complicated.…”
mentioning
confidence: 99%
“…In this work we have used high pressure techniques to investigate ways to improve their performance and extend their working temperature range. Since the band-gap and energy of the gain peak (E p ) increase with pressure at 0.126 meV/MPa [2] at constant temperature, when applied to edge emitting lasers (EEL) we can use pressure to determine the radiative and non-radiative recombination processes occurring [3]. In VCSELs, the pressure also tunes E p relative to the cavity mode energy E cm , which has a much weaker pressure dependence.…”
mentioning
confidence: 99%
See 1 more Smart Citation